Marketing trends and strategies in nutrition and health - Kuliková, Sofia; Bahles, Michael; Escobar Rios, Andrea; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
This thesis explores the impact of marketing strategies on consumer behaviors in the nutrition and health sector. Through a detailed analysis of existing case studies, it identifies successful tactics, patterns, and potential drawbacks in marketing campaigns. The aim of the study is to optimise strategies to increase consumer engagement and provide practical recommendations to bridge the gap between theory and practice.
Vedoucí práce: Michael Bahles
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses